Properties of Univalence for a New General Integral Operator Defined as a Joint Extension of Two Known Integral Operators. (27th March 2023) - Breaz, Nicoleta
Abstract : In this paper, we consider a new general integral operator, defined as a joint extension of two already known integral operators, and prove some univalence properties for this operator. Some other well-known operators are mentioned as particular cases of our general operator, and known results are outlined also as particular cases of our results.